1992
DOI: 10.1002/pd.1970120103
|View full text |Cite
|
Sign up to set email alerts
|

Nature and frequency of chromosomal abnormalities in pregnancies with abnormal ultrasound findings: An analysis of 117 cases with review of the literature

Abstract: During a 7-year period, 117 fetal karyotypes were available from 131 genetic amniocenteses. These procedures were performed between 14 and 37 weeks' gestation for the following abnormal ultrasound findings: (1) intrauterine growth retardation (IUGR)--61 cases; (2) fetal malformation--71 cases; and (3) amniotic fluid volume (AFV) abnormality--60 cases. Chromosomal abnormalities were identified in 19 cases (16.2 per cent). Aneuploidy was 2.5 times as frequent in the presence of malformations than in their absenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0
2

Year Published

1993
1993
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 28 publications
1
19
0
2
Order By: Relevance
“…Eight investigations focused on pregnancies undergoing invasive cytogenetic testing, a certain proportion of which were referred due to polyhydramnios. Two of these studies included all the referred samples (Shimada et al, 2009;Claussen et al, 1994), some required the presence of second trimester ultrasound (Yaman et al, 1996;Dombrowski et al, 1993), or focused only on pregnancies above 28 weeks (Drummond et al, 2003), two included only amniocenteses performed due to sonographic abnormality (Gagnon et al, 1992;Eydoux et al, 1989), and Lee et al analyzed only cases of idiopathic polyhydramnios (Lee et al, 1996). The remaining papers focused on patients diagnosed with polyhydramnios (a certain proportion of which underwent cytogenetic testing), besides Hentemann et al (Hentemann et al, 1989), who analyzed pregnancies with any ultrasonographic abnormality (including polyhydramnios).…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…Eight investigations focused on pregnancies undergoing invasive cytogenetic testing, a certain proportion of which were referred due to polyhydramnios. Two of these studies included all the referred samples (Shimada et al, 2009;Claussen et al, 1994), some required the presence of second trimester ultrasound (Yaman et al, 1996;Dombrowski et al, 1993), or focused only on pregnancies above 28 weeks (Drummond et al, 2003), two included only amniocenteses performed due to sonographic abnormality (Gagnon et al, 1992;Eydoux et al, 1989), and Lee et al analyzed only cases of idiopathic polyhydramnios (Lee et al, 1996). The remaining papers focused on patients diagnosed with polyhydramnios (a certain proportion of which underwent cytogenetic testing), besides Hentemann et al (Hentemann et al, 1989), who analyzed pregnancies with any ultrasonographic abnormality (including polyhydramnios).…”
Section: Resultsmentioning
confidence: 98%
“…For the comparisons of interrater reliability for study selection, the kappa coefficient was 0.95 during the abstract review (95% CI 0.90 to 0.99), and 0.92 in the full-text stage (95% CI 0.86 to 1.0). Finally, of 4297 initial references, twenty papers encompassing 1729 cases of idiopathic polyhydramnios were included in the review (Abele et al, 2012;Shimada et al, 2009;Drummond et al, 2003;Dashe et al, 2002;Biggio et al, 1999;Lee et al, 1996;Yaman et al, 1996;Barnhard et al, 1995;Hill et al, 1995;Claussen et al, 1994;Glantz et al, 1994;Dombrowski et al, 1993;Zahn et al, 1993;Brady et al, 1992;Gagnon et al, 1992;Hendricks et al, 1991;Carlson et al, 1990;Eydoux et al, 1989;Hentemann et al, 1989;Landy et al, 1987). Table 1 summarizes the studies' characteristics.…”
Section: Resultsmentioning
confidence: 99%
“…The association between fetal structural defects detected by ultrasound and chromosomal anomalies has been studied by many authors (Marchese et al, 1985;Palmer et al, 1987;Williamson et al, 1987;Wladimiroff et al, 1988;Eydoux et al, 1989;Hentemann et al, 1989;Rizzo et al, 1990;Van Zalen-Sprock et al, 1991;Gagnon et al, 1992;Nicolaides et al , 1992;Claussen et al, 1994) and all studies have uniformly reported a higher rate of chromosomal aberrations compared to neonatal studies (Kalter and Walkany, 1983).…”
Section: Introductionmentioning
confidence: 97%
“…We assumed that it has by now become generally recognized [16,17] that prenatal karyotyping should be carried out when a prenatal ultrasound test reveals the existence of a con genital anomaly and when the decision is made to termi nate a pregnancy. Consequently, karyotyping should be included in prenatal supervision programs rather than in postnatal examinations.…”
Section: Analysis O F Casesmentioning
confidence: 99%